Evaluating the structural effects of intra-articular sprifermin on cartilage and non-cartilaginous tissue alterations, based on sqMRI assessment over 2 years - Roemer, Frank; Kraines, J.; Aydemir, A.; Wax, S.; Hochberg, M. C.; Crema, M. D.; Guermazi, A. (Osteoarthritis and Cartilage, 2020)
Objective: Sprifermin (recombinant human fibroblast growth factor-18), a potential disease-modifying osteoarthritis (OA) drug, demonstrated dose-dependent effects on femorotibial cartilage thickness (by quantitative magnetic resonance imaging [MRI]) in the phase II FORWARD study. This post-hoc analysis evaluated the potential effects of sprifermin on several articular structures in the whole joint over 24 months using semi-quantitative MRI assessment. Design: Patients aged 40–85 years with symptomatic radiographic knee OA, Kellgren–Lawrence grade 2 or 3, and medial minimum joint space width ≥2.5 mm in the target knee were randomized (1:1:1:1:1) to receive three double-blinded, once-weekly, intra-articular injections of sprifermin 30 μg or 100 μg or placebo every 6 (q6mo) or 12 months. 1.5- or 3 T MRIs were read using the Whole-Organ Magnetic Resonance Imaging Score (WORMS) system at baseline and 24 months. Change from baseline at 24 months on compartment and/or whole knee level was assessed for cartilage morphology, bone marrow lesions (BMLs), and osteophytes by delta-subregional and delta-sum (DSM) approaches. Menisci, Hoffa-synovitis, and effusion-synovitis were also evaluated for worsening. Results: 549 patients were included. Dose-dependent treatment effects from baseline to 24 months were observed on cartilage morphology (sprifermin 100 μg q6mo vs placebo; mean DSM (95% confidence interval [CI]) −0.6 (−1.5, 0.2); less cartilage worsening) in the entire knee and BMLs sprifermin 100 μg q6mo vs placebo; mean DSM (95% CI) −0.2 (−0.5, 0.1) in the patellofemoral compartment. No effects over 24 months were observed on osteophytes, menisci, Hoffa-synovitis or effusion-synovitis. Conclusions: Positive effects associated with sprifermin were observed for cartilage morphology changes, and BML improvement. There were no meaningful negative or positive effects associated with sprifermin in the other joint tissues examined.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Knee; MRI; Sprifermin; Treatment; WORMS